A poromechanics model for plastic shrinkage of fresh cementitious materials. (July 2018) - Ghourchian, Sadegh; Wyrzykowski, Mateusz; Lura, Pietro
Abstract: When fresh cementitious materials are exposed to evaporation, drying of the pore fluid leads to capillary pressure development and plastic shrinkage. Plastic shrinkage occurring after the solid percolation threshold plays an important role in the initiation and propagation of plastic shrinkage cracks, which may compromise the durability and decrease the service life of concrete structures. In this study, a poromechanics approach to plastic shrinkage is developed. Novel experimental methods are utilized to quantify the material properties used as model input. An independent set of measurements is further used to validate the developed model. It is shown that the bulk modulus evolution plays a prominent role in controlling the plastic shrinkage of cementitious materials.